Theoretical research on heat transfer law during underground coal gasification channel extension process. (October 2019) - Xin, Lin; Cheng, Weimin; Xie, Jun; Liu, Weitao; Xu, Min
Graphical abstract: The gasification channel is divided into three zones in the axial direction of airflow movement, and extends into a trumpet-shaped form because of the different radial extension in three zones, so it's a thermal conduction of moving boundary condition around the UCG channel. The t ≧ 30 °C (or Δ t =10 °C) is considered as the criterion for the temperature field propagation range and the maximum is 2.22 m; the t ≧ 300 °C is considered as the criterion for the high temperature distribution range, and the maximum is 0.65 m. The temperature distribution ranges are affected by boundary temperature conditions and radial expansion rate. Highlights: An extension model of cylindrical channel has been established. The unsteady thermal conduction mathematical equation under moving coordinate system has been given. The maximum of temperature distribution range of t ≧ 30 °C (or Δ t = 10 °C) is 2.22 m. The maximum of high-temperature distribution range of t ≧ 300 °C is 0.65 m. The temperature distribution ranges are affected by boundary temperature conditions and radial extension rate. Abstract: In order to study the heat transfer issue of underground coal gasification (UCG) channel, an extension model of cylindrical channel was established to study the temperature distribution law of UCG channel during the entire gasification process (dry and distillation stage, reduction stage and oxidation stage) based on the Fourier heat transfer theory and the Laplace transform method. Considering the radial extension of gasification boundary, this issue is a thermal conduction of moving boundary condition, and the unsteady thermal conduction mathematical equation under the moving coordinate system was established, and assumes that the gasification channel boundary satisfies the first kind of boundary condition in the entire gasification process, and the boundary temperature changes in a piecewise linear manner. The secondary Laplace transform and inversion method was used to solve the temperature equations of all stages, and the analytical solutions, which contains the initial temperature distribution function w 1 η + u 2 τ or w 2 η + u 3 τ, were also obtained. The values and their changing laws of temperature propagation range ( t ≥ 30 °C, or Δ t ≥ 10 °C) and the high-temperature distribution range ( t ≥ 300 °C) were also given, and they are affected by the boundary temperature conditions and the radial extension rate of gasification channel.